2020
DOI: 10.1177/0269216319896747
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual needs and communicating about death in nonreligious theistic families in pediatric palliative care: A qualitative study

Abstract: Background: Spiritual support should be offered to all patients and their families regardless of their affiliated status with an organized religion. Aim: To understand nonreligious theistic parents’ spirituality and to explore how parents discuss death with their terminally ill children in mainland China. Design: Qualitative study. Setting/participants: This study was conducted in the hematology oncology center at Beijing Children’s Hospital. Participants in this study included 16 bereaved parents. Results: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 31 publications
(33 reference statements)
0
29
0
1
Order By: Relevance
“…Tools such as the Carer Support Needs Assessment Tool (CSNAT) can be used to identify specific carer support needs [25][26][27], and could enrich the quality of information on referral. Spiritual needs, in the broadest sense, were rarely documented, despite being important for patients and their families [28][29][30][31]. This may be due partly to the inclusion of an explicit section about spiritual support needs on some but not all referral form templates.…”
Section: Discussionmentioning
confidence: 99%
“…Tools such as the Carer Support Needs Assessment Tool (CSNAT) can be used to identify specific carer support needs [25][26][27], and could enrich the quality of information on referral. Spiritual needs, in the broadest sense, were rarely documented, despite being important for patients and their families [28][29][30][31]. This may be due partly to the inclusion of an explicit section about spiritual support needs on some but not all referral form templates.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these states is critical to the provision of effective support, since there is no consistency as to how religious affiliations across cultures impact grief in parents. For instance, South American families reported that their spirituality [95] was compromised by evangelical family and/or friends [96] whilst self-reported nonreligious participants in Beijing found religious mores a source of support that enhanced spirituality [97]. Similarly, whilst Hedayat [98] suggested that in Muslim societies the death of a child a reinforced their religious faith [92], some bereaved parents believed that their child's death was a punishment from a Higher Power [89,99,100] and turned their disappointment inward and or towards the Higher Power [99].…”
Section: Resultsmentioning
confidence: 99%
“…This is underlined by the knowledge that factors previously deemed supportive to coping and meaning-making may turn into risk factors and vice versa. With Knapp and Contro [ 95 ], Jonas, Scanlon [ 96 ], van der Geest, van den Heuvel-Eibrink [ 151 ] and Cai, Guo [ 97 ] highlighting the interchangeability of factors listed in either column in Table 3 , data here suggests that the RToP’s ability to capture such change ought to be used in the training of healthcare professionals so that they are better able to respond appropriately to each individual parent’s bereavement needs [ 27 30 , 33 , 34 , 195 ]. Addressing change in the rings of the RToP foregrounds the import of timely [ 57 ] and context sensitive [ 7 ] assessments of parental coping [ 25 , 89 , 196 , 197 ] and careful involvement of various members of the bereaved parents’ friends, relatives and community.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual needs, in the broadest sense, were rarely documented, despite being important for patients and their families. [23][24][25][26] An indication of the importance of spiritual support for the terminally ill person at the time of referral, might usefully ensure that the person is directed towards the hospice service(s) most aligned with their needs.…”
Section: Discussionmentioning
confidence: 99%